Meanings are acquired from experiencing differences against a background of sameness, rather than from experiencing sameness against a background of difference: Putting a conjecture to the test by embedding it in a pedagogical tool - Marton, Ference; Pang, Ming Fai (Frontline Learning Research, 2013)
In helping learners to make a novel meaning their own, such as when helping children to understand what a word means or teaching students a new concept in school, we frequently point to examples that share the aimed-at meaning but differ otherwise. This type of approach rests on the assumption that novel meanings can be acquired through the experience of sameness against a background of difference. This paper argues that this assumption is unfounded and that the opposite is the case: we make novel meanings our own through the experience of differences against a background of sameness. We put this conjecture to the test in an experimental study by embedding it in a computer game and the results support the conjecture.